Mental Healthcare of Elderly Population of Bangladesh: Current Situation and Challenges - Tanira, Shaorin; Shahriah, Sunjida; Amin, Raihana; Sharmin, Saida; Shaikh, Muhammad Abdul Kayum; Taha, Samnun F. (Journal of Psychiatrists’ Association of Nepal, 2022)
In Bangladesh, mental health of elderly people is often underestimated because of lack of awareness and perceived needs of medical care for physical health problems, whereas comorbid psychiatric conditions remain underdiagnosed among individuals in the country. Large numbers of older persons face challenges such as discrimination, negligence and abuse that severely restrict their human rights and their contribution to society. However, in recent times, NGOs, legislatives, and citizens argue that it is the high time that older persons should be identified as a distinct category deserving special care and attention under human rights law. In Bangladesh, about 14 million older adults live in the country, which is 7.7% of the total population; this ageing population has been projected to be 17.2 million by 2025. The Mental Health Act was passed by the National Parliament of Bangladesh in 2018. A multi-disciplinary working group with representatives from government Ministries, mental health professional organizations, and advocacy groups collaborated to draft a National Mental Health Policy, which was approved by the Ministry of Health in 2019 is currently awaiting endorsement by the Cabinet. The working group also drafted a National Mental Health Strategic Plan 2020- 2030, anticipating implementation over the next decade, through successive 5-year action plans. To date, neither the policy nor the strategic plan has been implemented. Adoption of the strategic plan within the MOHFW general health care plan is anticipated in 2020. Under the circumstances, this review paper aims to examine current situation and challenges in having access to mental health care for the elderly people as part of human rights and a public health concern, while the health system has already been overburdened with other public health challenges due to limited resources.